Validity of Project Based Integrated Environmental Science Problem Learning (PBIESPL) Model with Authentic Assessment - Hairida, Hairida; Hadi, Lukman; Kurniasih, Dedeh (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2022)
This study aims to develop a learning model that can improve students' collaboration and communication skills. The learning model developed is called the PBIESPL (Project Based Integrated Environmental Science Problem Learning) with authentic assessment. This study used reseach and development methods with reference to Borg and Gall consisting of preliminary study, development, and testing. The validity of the learning model was carried out by 20 science learning experts and analyzed using the Lawshe method. The results of the validity test of the PBIESPL learning model with authentic assessment showed an average CVR = 0.99, which means it is very valid. Â Based on the results of this study, it is known that the PBIESPL learning model with authentic assessments can be implemented by educators in their classroom learning because it can improve studentsâ€™ collaboration and communication skills and then can facilitate educators in assessing student skills.